﻿The comparison between different over-the-counter drugs Analgesics used to relive cramps pain associated with menstrual cycle for females in Jordan on kidney function - Saif Aldeen Jaber; Moeen Dababneh; Mohamed Saadah (Pensoft Publishers, 2022)
Primary dysmenorrhea is an abdomen cramps caused pain for females under menstrual cycle. The majority of females in Jordan are consuming paracetamol and different types of NSAIDs to relive the mentioned pain. In this study a different group of females between ages 18-24 years old either not consuming any analgesic or consuming paracetamol, ibuprofen, or diclofenac salts have been asked to test the blood creatinine concentration after 10 days of consumption and after 5 and 10 days of discontinuation. SPSS analysis technique was used to analyse the results. As a results, consuming of paracetamol for 10 days show similar creatinine clearance for females without consuming any type of analgesics. While ibuprofen and diclofenac salts show change in kidney function after the 10 days of consumption. Ibuprofen normal kidney function was for 94.1% of the females where only 0.9% of the females show a sign of acute renal failure. On the other hand, the females using diclofenac salts show a high percentage of 61.2% with a sign of acute renal failure. Most of females show restored renal function after discontinuation of analgesics for 5 or 10 days. In conclusion, the consumption of analgesics between females should be monitored while the using of diclofenac salts should be considered as a prescribed drug due to the major and serious adverse drug reactions caused by the daily consumption.